THE PHYSICAL SELF-CONCEPT DURING THE LIFE SPAN - Esnaola Etxaniz, Igor (Anales de Psicología / Annals of Psychology, 2008)
The main purpose of this research is analysed the physical self-concept during the life span. The sample consists of 1.259 participants: 627 adolescents (12-18 years old), 271 young people (19-30 years old), 248 adults (31-49 years old) and 112 persons with more than 55 years old. In females and males, the results show that the perceptions of physical ability and physical condition scales go decreasing from adolescence to older people; and, in female sample the perceptions in attractive and physical self-concept scales go increasing from adolescence to older people.